2018
DOI: 10.23860/dignity.2018.03.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Decriminalization of Prostitution: The Soros Effect

Abstract: This article explores the activities of George Soros and his charitable organization, Open Society Foundations (OSF), in advocating for the full decriminalization of the sex trade industry. Research finds that OSF spends only a small amount of money on grass roots "sex worker" groups around the world advocating for full decriminalization, but the foundation awards larger amounts of funds to large human rights groups whose reports and policies have a wider reach. OSF's rationale for full decriminalization fails… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Cunningham and Shah (2018) [52], for example, found that the decriminalization of indoor sex work in a Rhode Island community did increase the overall size of the market (specifically, there were more participants and more exchanges) but resulted in fewer reported rape offenses and fewer reported sexually transmitted infections by the sex sellers. Raphael (2018) [53], however, found that decriminalization leads to more sex trafficking, primarily because the traffickers see decriminalized sex markets as safer and more lucrative. In fact, the frequency of sex sellers that are also or were also victims of human trafficking is high; with some research finding that prostitution is the primary or only motive behind most trafficking cases in the United States [54][55][56].…”
Section: Commercial Sex In Urban Areasmentioning
confidence: 99%
“…Cunningham and Shah (2018) [52], for example, found that the decriminalization of indoor sex work in a Rhode Island community did increase the overall size of the market (specifically, there were more participants and more exchanges) but resulted in fewer reported rape offenses and fewer reported sexually transmitted infections by the sex sellers. Raphael (2018) [53], however, found that decriminalization leads to more sex trafficking, primarily because the traffickers see decriminalized sex markets as safer and more lucrative. In fact, the frequency of sex sellers that are also or were also victims of human trafficking is high; with some research finding that prostitution is the primary or only motive behind most trafficking cases in the United States [54][55][56].…”
Section: Commercial Sex In Urban Areasmentioning
confidence: 99%
“…La prostitución legal en Nevada ha sido estudiada de modo exhaustivo (Brents y Hausbeck, 2007;Brents y col., 2010;Seals, 2015;Brents, 2016;Raphael, 2018;Blithe y col., 2019;Walks, 2019), así como la prostitución ilegal autóctona (Farley, 2007;Wagner y col., 2016;Macfarlane y col., 2017). Por otra parte, son numerosas las investigaciones realizadas en México sobre las técnicas de neutralización utilizadas para minimizar la responsabilidad de quienes trafican mujeres para la prostitución.…”
Section: Ciencias Socialesunclassified